Assessment of the Effects of Holding Time and Temperature on Escherichia coli Densities in Surface Water Samples - Pope, Misty L. (American Society for Microbiology, 2003)
Escherichia coli is a routinely used microbiological indicator of water quality. To determine whether holding time and storage conditions had an effect on E. coli densities in surface water, studies were conducted in three phases, encompassing 24 sites across the United States and four commonly used monitoring methods. During all three phases of the study, E. coli samples were analyzed at time 0 and at 8, 24, 30, and 48 h after sample collection. During phase 1, when 4°C samples were evaluated by Colilert or by placing a membrane onto mFC medium followed by transfer to nutrient agar containing 4-methylumbelliferyl-β-d-glucuronide (mFC/NA-MUG), three of four sites showed no significant differences throughout the 48-h study. During phase 2, five of seven sites showed no significant difference between time 0 and 24 h by membrane filtration (mFC/NA-MUG). When evaluated by the Colilert method, five of seven sites showed no significant difference in E. coli density between time 0 and 48 h. During phase 3, 8 of 13 sites showed no significant differences in E. coli densities between time 0 and the 48-h holding time, regardless of method. Based on the results of these studies, it appears that if samples are held below 10°C and are not allowed to freeze, most surface water E. coli samples analyzed by commonly used methods beyond 8 h after sample collection can generate E. coli data comparable to those generated within 8 h of sample collection. Notwithstanding this conclusion, E. coli samples collected from surface waters should always be analyzed as soon as possible.